2016
DOI: 10.1128/jvi.00771-16
|View full text |Cite
|
Sign up to set email alerts
|

Functional Upregulation of the DNA Cytosine Deaminase APOBEC3B by Polyomaviruses

Abstract: The APOBEC3 family of DNA cytosine deaminases has important roles in innate immunity and cancer. It is unclear how DNA tumor viruses regulate these enzymes and how these interactions, in turn, impact the integrity of both the viral and cellular genomes. Polyomavirus (PyVs) are small DNA pathogens that contain oncogenic potentials. In this study, we examined the effects of PyV infection on APOBEC3 expression and activity. We demonstrate that APOBEC3B is specifically upregulated by BK polyomavirus (BKPyV) infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
110
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(120 citation statements)
references
References 43 publications
(69 reference statements)
10
110
0
Order By: Relevance
“…Considering this, it is unusual that there is no strong evidence of APOBEC3 family upregulation or activity in MCPyV-positive tumors. A recent study also demonstrated that another human polyomavirus, BK polyomavirus, is able to upregulate APOBEC3B in infections of primary renal tubule epithelial cells and that this is at least partially mediated by large T antigen expression (7). This same study also demonstrated that MCPyV large T antigen is able to upregulate APOBEC3B in this cell culture system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering this, it is unusual that there is no strong evidence of APOBEC3 family upregulation or activity in MCPyV-positive tumors. A recent study also demonstrated that another human polyomavirus, BK polyomavirus, is able to upregulate APOBEC3B in infections of primary renal tubule epithelial cells and that this is at least partially mediated by large T antigen expression (7). This same study also demonstrated that MCPyV large T antigen is able to upregulate APOBEC3B in this cell culture system.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of this integration event and the constitutive expression of viral proteins on the host genome structure and somatic mutation profile of the tumor genome have not been studied in depth. Using in vitro models, it has been suggested that expression of full-length MCPyV large T antigen is able to disrupt the stability of the host genome and upregulate the mutagenic enzyme APOBEC3B (6, 7). Another small DNA tumor virus, human papillomavirus (HPV), also triggers the upregulation of the DNA cytosine deaminase APOBEC3B and is likely responsible for the majority of mutations observed in HPV-positive cervical, head and neck squamous cell, and bladder carcinomas (812).…”
Section: Introductionmentioning
confidence: 99%
“…These results mirror prior studies on human A3G and A3F, where 20 and 19 lysines were simultaneously converted to arginine, and the K-less variants resisted Vif-mediated degradation (Albin et al, 2013; Dang et al, 2008; Shao et al, 2010). Since A3B may very well restrict the replication of other viruses, including HBV, HPV, and HTLV (Ahasan et al, 2015; Lucifora et al, 2014; Ooms et al, 2012; Starrett et al, 2016; Starrett et al, 2017; Verhalen et al, 2016; Vieira et al, 2014; Warren et al, 2015), it is likely that additional A3B counteraction strategies exist and that the functional K-free construct described here may be useful as a mechanistic probe. The K-free enzyme may also be useful for future studies investigating A3B cellular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…First, although A3B does not appear to overtly restrict the replication of polyomaviruses and papillomaviruses, the preferred 5′-TC ssDNA target motifs of A3B are depleted from these viral genomes and the predicted 5′-TT product is enriched implying continual selective pressure (Ahasan et al, 2015; Starrett et al, 2016; Starrett et al, 2017; Verhalen et al, 2016; Vieira et al, 2014; Warren et al, 2015). Moreover, both of these small DNA viruses specifically upregulate A3B at the transcriptional level (Mori et al, 2017; Starrett et al, 2017; Verhalen et al, 2016; Vieira et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation